Dual‐Acting Small‐Molecule Inhibitors Targeting Mycobacterial DNA Replication. Issue 47 (27th July 2020) - Singh, Meenakshi; Ilic, Stefan; Tam, Benjamin; Ben‐Ishay, Yesmin; Sherf, Dror; Pappo, Doron; Akabayov, Barak
Abstract: Mycobacterium tuberculosis ( Mtb ) is a pathogenic bacterium and a causative agent of tuberculosis (TB), a disease that kills more than 1.5 million people worldwide annually. One of the main reasons for this high mortality rate is the evolution of new Mtb strains that are resistant to available antibiotics. Therefore, new therapeutics for TB are in constant demand. Here, we report the development of small‐molecule inhibitors that target two DNA replication enzymes of Mtb, namely DnaG primase and DNA gyrase (Gyr), which share a conserved TOPRIM fold near the inhibitors' binding site. The molecules were developed on the basis of previously reported inhibitors for T7 DNA primase that bind near the TOPRIM fold. To improve the physicochemical properties of the molecules as well as their inhibitory effect on primase and gyrase, 49 novel compounds have been synthesized as potential drug candidates in three stages of optimization. The last stage of chemical optimization yielded two novel inhibitors for both Mtb DnaG and Gyr that also showed inhibitory activity toward the fast‐growing non‐pathogenic model Mycobacterium smegmatis ( Msmg ). Abstract : Full stop : The bacterium Mycobacterium tuberculosis is responsible for tuberculosis and is one of the most prevalent killers among single infectious agents. In this report, we describe the rational design of first‐in‐class small molecules that inhibit the activity of two DNA replication enzymes of M. tuberculosis, namely DnaG primase and DNA gyrase, which serve as selective targets for the design of anti‐tuberculous agents (see figure).